Complete plastome sequence of Torenia concolor Lindley (Linderniaceae): an ornamental herb. Issue 2 (3rd July 2019) - Cheng, Xia-Lan; Li, Hai-Li; Wang, Hong-Xin; Nizamani, Mir Mohammad; Chen, Yan
Abstract: In this study we firstly reported the complete chloroplast genome of Torenia concolor, a species of Linderniaceae. The complete chloroplast genome of T. concolor is 153, 853 bp in length with a typical quadripartite structure, consisting of a large single-copy region (LSC, 85, 446 bp), a single-copy region (SSC, 18, 837 bp), and a pair of inverted repeats (IRs, 24, 785 bp). There are 114 genes annotated, including 80 unique protein-coding genes, 4 unique ribosomal RNA genes, and 30 transfer RNA genes. To investigate the evolution status of T. concolor, as well as Linderniaceae, we constructed a phylogenetic tree with T. concolor and other 16 species based on their complete chloroplast genomes. According to the phylogenetic topologies, T. concolor was closely related to Pedicularis hallaisanensis .